Modeling of Buck Converter Models in MPPT using PID and FLC - Chandani Sharma; Anamika Jain (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2015)
PV has become universal for power utility applications in comparison to conventional technologies when it comes to economic competitiveness. As the efficiency of solar PV panel is low, it becomes mandatory to extract maximum power from the PV panel at any given period of time. Maximum Power and efficiency in Photovoltaics can be improved by Maximum Power Point tracking even under distributed temperature and irradiance functions. The paper attempts to compare two different Buck converter models based on predictive control. The two converter models using State space differential equation and direct component in MATLAB/SIMULINK are optimized through PID and FLC to obtain increased gain and desired converter output. A PV system connected with Buck converter using an intelligent controller (FLC) for extracting maximum power at different environmental conditions is proposed and the results are compared with conventional PID controller.